MANAJEMEN MEDIA INFOSIAK.COM DALAM MEMBERIKAN INFORMASI DI KABUPATEN SIAK - Tika Lestari; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The newsreader is the parties who receives or use the information. Information required by the user aims to increase knowledge, and improve skills that ultimately can change attitudes and behavior. In presenting a news portal certainly provides a decent news presentation for its readers, not least the news portal Infosiak.com provide information for the community. Infosiak.com is an online news portal that provides information about the development of Siak in particular. The problem raised in this research is how media management Infosiak.com in providing information in Siak District.This research use descriptive qualitative method, while the object of the research is Infosiak.com media management in providing information in Siak District and research subjects include editorial leaders, journalists and the public. Data collection techniques used are interviews, observation, and documentation.The results found First, the plan to produce the main product of news that will be published on news portals, and published to social media Facebook and Twitter. Second, the organization of Infosiak.com has placed each personal in the right position with their expertise in respectively. Third, the implementation includes news coverage, news writing and the latest news uploading in use with the existence of social media like Facebook and Twitter. Fourth, the supervision made Infosiak.com one of them is the evaluation of the work of supervision of news material to be posted. In addition Infosiak.com also opened a service to provide criticism and suggestions from the public via e-mail.Keywords : Media Infosiak.com, Information, Community Siak District